Effect of chemical treatments on the mechanical properties of peanut shell and cement blends - M. Gatani; R. Argüello; S. Sesín (Materiales de Construccion, 2010)
An abundance of agri-food waste in the area around Cordoba, Argentina, has driven the development of new construction materials. This study explored the applicability of peanut shells as additions in cement blends and the suitability of the properties of the resulting mixes for use in construction materials.